Students’ online purchase frequency: Investigating perceived enjoyment as a bridge between usefulness, ease of use and behavior - Akup, Noorhafizah (Jurnal Penyelidikan Sains Sosial, 2026)
The study investigates the influence of perceived usefulness (PU), perceived ease of use (PEOU), and perceived enjoyment (PE) on students’ online purchase frequency, with perceived enjoyment acting as a mediating variable. With the fast-paced growth of e-commerce, understanding the factors that drive students’ online purchasing behavior is essential for both marketers and educators. This study employed quantitative research design, with data gathered through a structured questionnaire distributed to 279 students from the Commerce Department. The data were analyzed using PLS-SEM via SmartPLS 4. The findings reveal that perceived usefulness and perceived enjoyment have significant positive effects on online purchase behavior, indicating that students tend to shop online more frequently when they perceive the activity as both beneficial and enjoyable. In contrast, perceived ease of use showed no significant direct effect on online purchase behavior, suggesting that students are already familiar with using online shopping platforms. However, perceived ease of use demonstrated a strong positive effect on perceived enjoyment. Mediation analysis confirmed that perceived enjoyment partially mediated the relationships between both perceived usefulness and perceived ease of use with online purchase behavior. The model explained 41.8% of the variance in online purchase behavior and 60.2% in perceived enjoyment, indicating moderate explanatory power. These findings underscore the importance of enhancing perceived enjoyment and usefulness to foster more engaging and satisfying online shopping experiences for students. This study contributes to the growing literature on digital consumer behavior and offers practical insights for e-commerce marketers targeting student populations.